Improving the Capability for Real Time Assessment of Roof Conditions through Intelligent Roof Bolt Drilling Operations, - Robert Anderson (International Conference on Ground Control in Mining, 2007)
Advance knowledge of roof conditions can lead to improvement in roof control strategies that will reduce roof falls and ultimately will reduce injuries to mine workers. J.H. Fletcher and Company, in cooperation with West Virginia University, has been developing a system to meet these needs by collecting torque, thrust, and rotation speed data during drilling operations. Recent improvements in analysis algorithms to detect anomalies in the roof structure as well as various display enhancements for real time mapping and evaluation of roof structures have been incorporated into current Fletcher Information Display system. The unit has also been housed in an explosion-proof container to allow use in coal mine applications. Recently, the system has undergone extensive field trials in several limestone mines and one coal mine. During these trials, the National Institute for Occupational Safety and Health assisted Fletcher in verifying the accuracy of the roof mapping capability of the system by comparing the display information to bore hole scoping observations and drill corings. It was concluded from this assessment that the intelligent drilling system can complement scoping and core analysis to provide a more complete picture of roof strata and is capable of seeing features or conditions that are not always obvious in these more traditional methods.